Pemodelan Sistem Informasi Pengelolaan Dokumen Online Untuk Sistem Penjaminan Mutu Internal Pada Politeknik Jambi - Fortia magfira (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2022)
Documents at a tertiary institution are one of the important factors in the internal quality assurance system to measure the level of achievement of organized activities within the tertiary institution. ‘Documents ‘can ‘be ‘used‘ as‘ a ‘reference‘ in ‘making decisions, formulating policies, ‘planning, ‘regulation, ‘monitoring ‘or ‘monitoring ‘the ‘achievements ‘of ‘activities ‘and ‘evaluating these activities. Document management at the Jambi Polytechnic is carried out using a file sharing system. The use of file sharing in document management results in limitations on document storage and access by stakeholders, where stakeholders can only store and access documents using the local network at the Jambi Polytechnic. This has hampered the process of decision making, policy formulation, planning, regulation, monitoring by stakeholders when they are not connected to the Jambi Polytechnic local network. Existing problems can be solved by having an information system that is devoted to managing documents in the form of storing and accessing documents at the Jambi Polytechnic. Modeling an online document management information system can be used as a reference before developing an information system. Modeling of this document information system will be carried out by means of visual modeling which will give an overview of how the components are connected and interact so that detailed information from an information system can be seen clearly.